2021
DOI: 10.1126/sciadv.abf1913
|View full text |Cite
|
Sign up to set email alerts
|

Robust information routing by dorsal subiculum neurons

Abstract: The dorsal hippocampus conveys various information associated with spatial navigation; however, how the information is distributed to multiple downstream areas remains unknown. We investigated this by identifying axonal projections using optogenetics during large-scale recordings from the rat subiculum, the major hippocampal output structure. Subicular neurons demonstrated a noise-resistant representation of place, speed, and trajectory, which was as accurate as or even more accurate than that of hippocampal C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 90 publications
10
71
0
Order By: Relevance
“…axis versus boundary vector cells) to LR cells interacts with thalamic head direction inputs. Very recent work on understanding the tuning properties of subicular cells in a projection-specific manner will help to narrow the functional range of possible dorsal subicular inputs to LR cells ( Kitanishi et al, 2021 ). We anticipate that one key impact of dorsal subicular inputs to LR cells will be to impose a spatial filter on the angular speed and directional predictions stated above.…”
Section: Discussionmentioning
confidence: 99%
“…axis versus boundary vector cells) to LR cells interacts with thalamic head direction inputs. Very recent work on understanding the tuning properties of subicular cells in a projection-specific manner will help to narrow the functional range of possible dorsal subicular inputs to LR cells ( Kitanishi et al, 2021 ). We anticipate that one key impact of dorsal subicular inputs to LR cells will be to impose a spatial filter on the angular speed and directional predictions stated above.…”
Section: Discussionmentioning
confidence: 99%
“…ICA results that were significantly correlated with behavior, on average weighted the dSub contribution higher than any other brain region and dSub was one of the only individual brain regions that was significantly correlated with behavioral performance, despite pTau densities that were lower than 6 of the 7 other brain regions. Sub is one of the major outputs of CA1 and entorhinal cortex, and passes information to cortical areas, including RSC (Kitanishi et al, 2021). Previous research has shown that Sub can be partitioned into two regions, distal Sub and proximal Sub, which have been shown to be structurally and functionally different.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Sub neurons have been shown to represent spatial information, such as place, speed, and trajectory, as accurately, or even more so, than CA1. An important role of Sub may be to create noise-resistant, high-firing rate, accurate representations for multiple types of navigational information (Kitanishi et al, 2021). Thus, Tau accumulation in Sub may be a critical driver of early hippocampal-parietal network dysfunction leading to the emergence of impaired spatial navigation in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Both the CLA and ACC are heavily implicated in a range of non-spatial behaviors often described as being “cognitive” or “mnemonic” in function (Botvinick, 2007; Brown and Braver, 2005; Carter et al, 1998; Devinsky et al, 1995; Kim et al, 2016; Mohanty et al, 2007; Smith et al, 2012; Smythies et al, 2012; Stevens et al, 2011), but there is also evidence that these regions exhibit some degree of spatial information processing (Guterstam et al, 2015; Jankowski and O’Mara, 2015; Sutherland et al, 1988; Whishaw et al, 2001). Indeed, 7-15% of cells in the claustrum were found to encode place or boundary-related information (Jankowski and O’Mara, 2015), though this percentage is relatively low compared to the 60% of anterior thalamic (Taube, 1998) and 61% of dorsal subicular (Kitanishi et al, 2021) neurons that are known to clearly encode elemental direction, place, and other spatial features. Regardless, retrosplenial RS neurons may be receiving direct spatial inputs from the CLA and ACC in addition to the cognitive and mnemonic information relayed by these two regions.…”
Section: Discussionmentioning
confidence: 99%